INOVASI MANAJEMEN SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN DI MADRASAH ISTIQLAL JAKARTA - Muhamad Alwi (el-Moona: Jurnal Ilmu Pendidikan Islam, 2022)
This study aims to determine the innovation of school management in improving the quality of education at Madrasah Istiqlal Jakarta (MIJ). The method used in this research is a qualitative approach. Informants in this study consisted of directors, heads of sections, and heads of education units. This type of research method is qualitative. Data collection techniques through observation, documentation and interviews were tested by triangulation. The results of this study indicate that school management innovation in improving the quality of education at Madrasah Istiqlal Jakarta in the form of implementing ISO 21001: 2018, has a positive impact on all stakeholders at Madrasah Istiqlal Jakarta. This is evidenced by the increasing service provided, both teachers in providing teaching services and education personnel in providing services to parents and the community. Likewise, the level of attendance of educators and education is getting better. The implications of implementing this system include the creation of synergies in the need for madrasa accreditation, improving the image of madrasas, improving program quality, and improving education services.